If (7a+8b) (7c-8d) = (7a-8b) (7c+8d); then prove that a:b = c:d

Asked by brijt66 | 5th Aug, 2021, 06:28: AM

Expert Answer:

(7a+8b) (7c-8d) = (7a-8b) (7c+8d)
49ac-56ad+56bc-64bd = 49ac+56ad-56bc-64bd
-56ad+56bc= +56ad-56bc
ad=bc
a/b = c/d
a:b=c:d
(7a+8b) (7c-8d) = (7a-8b) (7c+8d)
49ac-56ad+56bc-64bd = 49ac+56ad-56bc-64bd
-56ad+56bc= +56ad-56bc
ad=bc
a/b = c/d
a:b=c:d(7a+8b) (7c-8d) = (7a-8b) (7c+8d)
49ac-56ad+56bc-64bd = 49ac+56ad-56bc-64bd
-56ad+56bc= +56ad-56bc
ad=bc
a/b = c/d
a:b=c:d

Answered by Arun | 5th Aug, 2021, 09:26: AM